Contribution of reversible histone acetylation to freeze tolerance and recovery in wood frog kidneys - Olawale O. Taiwo; Kenneth B. Storey (Scientific Reports)
Abstract The wood frog (Rana sylvatica) possesses remarkable adaptation mechanisms that ensures it survival in extreme environmental conditions, including enduring whole body freezing. The present study investigates the epigenetic mechanisms, specifically histone lysine acetylation and deacetylation, which are critical for regulating gene expression and conserving energy, underlying the wood frog’s ability to endure whole-body freezing. We investigated the expression patterns of lysine acetyltransferases (KATs) and lysine deacetylases (HDACs) in wood frog kidney over the freeze-thaw cycle. Our results reveal a significant downregulation of KATs in kidneys of frozen frogs, with specific KATs showing considerable reductions. This suggests that histone acetylation may play a vital role in suppressing gene expression and conserving energy during freezing. Furthermore, histone acetylation marks, including H2AK5ac, H2BK5ac, H3K9ac, H3K23ac, H3K27ac, and H3K56ac, showed repression under frozen and thawed conditions, indicating a role in silencing specific genes. HDACs exhibited dynamic regulation, with HDAC3 and HDAC11 showing significant repression in frozen frog kidneys, while HDAC5, p-HDAC4, and p-HDAC8 were downregulated during the recovery phase, suggesting their involvement in the thawing process. This research provides crucial insights into the epigenetic control of freeze tolerance in wood frog kidneys and offers a foundation for further exploration of epigenetic modifications that mediate the wood frog’s remarkable adaptations for freezing survival.